Jung's seminar on Nietzsche's Zarathustra - Jung, C. G. (Carl Gustav), 1875-1961 (Princeton University Press, 1998)
Nietzsche's infamous work Thus Spake Zarathustra is filled with a strange sense of religiosity that seems to run counter to the philosopher's usual polemics against religious faith. For some scholars, this book marks little but a mental decline in the great philosopher; for C.G. Jung, Zarathustra was an invaluable demonstration of the unconscious at work, one that illuminated both Nietzsche's psychology and spirituality and that of the modern world in general. The original two-volume edition of Jung's lively seminar on Nietzsche's Zarathustra has been an important source for specialists in depth psychology. This new abridged paperback edition allows interested readers to participate with Jung as he probes the underlying meaning of Nietzsche's great work
Abridged ed. of: Nietzsche's Zarathustra. 1988
Keywords: Nietzsche, Friedrich Wilhelm, -- 1844-1900. -- Also sprach Zarathustra.; Nietzsche, Friedrich Wilhelm, -- 1844-1900 -- Psychology.; Nietzsche, Friedrich Wilhelm, -- 1844-1900 -- Also sprach Zarathustra.; Nietzsche, Friedrich Wilhelm, -- 1844-1900 -- Psychologie.; Nietzsche, Friedrich Wilhelm, -- 1844-1900; Also sprach Zarathustra (Nietzsche, Friedrich Wilhelm); Superman (Philosophical concept); Jungian psychology.; Surhomme.; Psychologie analytique.; PSYCHOLOGY -- Movements -- Psychoanalysis.; Jungian psychology; Psychology